(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
Early Permian (Sakmarian) crinoids are described from six horizons in the Saiwan Formation of the Huqf area of southeastern Oman. Each horizon yielded only one to three taxa. All specimens lived in a shallow water environment characterized by mixed siliciclastic or siliciclastic-carbonate sedimentation. Disarticulated arm plates of an indeterminate articulate crinoid are described from a tempestite bed in the Khuff Formation (Wordian) of the Haushi area. The Saiwan Sakmarian crinoids are some of the earlier, although not the earliest Permian crinoids known. Representatives of both primitive (sycocrinids) and advanced (scytalocrinids, blothrocrinids, texacrinids, and cromyocrinids) cladids and articulates are present in the Saiwan crinoids that are dominated by advanced dendrocrinids and belong to families previously reported from the Carboniferous or Permian. They show greatest affinity to the late Sakmarian/early Artinskian fauna from the Callytharra Formation of Western Australia. New taxa described herein double the number of genera (three) previously reported from the same area. The diversity of the Saiwan crinoids is relatively low when compared to the large faunas reported from Timor, Western Australia, Russia, and North America. However, they show affinity with each of the larger faunas. New taxa described are Coeliocrinus arenaceous n. sp., Moapacrinus? omanensis n. sp., Huqficrinus biserialis n. gen. and sp., and Campbellicrinus nodosus n. sp.